PERAN PEMERINTAH DALAM MENCEGAH PRAKTEK MONOPOLI JASA PELAYANAN EKSPOR BENIH LOBSTER - Muhamad Nur Iman Santoso (2023)
One form of business activity that is prohibited in business competition law is monopoly practice which is a form of market control. One of the cases of monopolistic practice is related to lobster seed export services involving the freight forwarder company PT. Aero Citra Kargo. This study aims to examine the government's role in preventing monopolistic practices and the responsibilities of freight forwarder companies that carry out these monopolistic practices. This research uses normative juridical research methods. namely through a literature study with a statutory and case approach. The results of this study indicate that the government's role, namely the KPPU, has not been maximized in preventing monopoly on the export of lobster seeds, which can be seen from the KPPU's delay in realizing the existence of monopolistic practices carried out by freight forwarder companies. KPPU has conducted studies with several parties related to the export of lobster seeds and did not find any regulations that designate only one company that can export. However, the fact is that only PT. ACK can perform exports. Companies that carry out monopolistic practices have been found guilty of violating Article 17 of Law Number 5 of 1999 in the KPPU decision Number 04/KPPUI/2021 and are responsible for stopping their business activities and confiscating assets for the state.